2020
DOI: 10.1002/cbf.3494
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA CCDC66 facilitates abdominal aortic aneurysm through the overexpression of CCDC66

Abstract: Funding information The fifth group of bosom friends and talents plan of Hanyang District, Wuhan Abdominal aortic aneurysm (AAA) is fatal meanwhile unpredictable asymptomatic cardiovascular disease. Available data suggests the potential participation of circular RNAs (circRNAs) in AAA pathogenesis. But direct evidence is limited. The present study is to functionally and mechanically characterize circRNA CCDC66 (circCCDC66) in AAA. Previous work indicated the differentially expressed circCCDC66 in AAA. At molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 30 publications
(54 reference statements)
0
23
0
Order By: Relevance
“…circCBFB facilitates VSMC proliferation and inhibits VSMC apoptosis via the circCBFB/miR-28-5p/GRIA4/LYPD3 axis ( 58 ). circCCDC66 sponges miR-342-3p to upregulate its host gene CCDC66 in VSMCs and regulates VSMC apoptosis and proliferation ( 59 ). These newly identified mechanisms may provide novel options for the treatment of aneurysm.…”
Section: Circrna As Cerna In Cvdsmentioning
confidence: 99%
“…circCBFB facilitates VSMC proliferation and inhibits VSMC apoptosis via the circCBFB/miR-28-5p/GRIA4/LYPD3 axis ( 58 ). circCCDC66 sponges miR-342-3p to upregulate its host gene CCDC66 in VSMCs and regulates VSMC apoptosis and proliferation ( 59 ). These newly identified mechanisms may provide novel options for the treatment of aneurysm.…”
Section: Circrna As Cerna In Cvdsmentioning
confidence: 99%
“…In line with the above results, Wang et al examined the competitive endogenous RNA (ceRNA) mechanism related to certain apoptotic circRNAs. For instance, two miRNAs (mmu-let-7a-2-3p and mmu-miR-199a-3p) of differentially expressed mmu_circRNA_001265 and their response elements were Oxidative Medicine and Cellular Longevity To prove the role of circRNA CCDC66 in the pathogenesis of AAAs and identify its corresponding pathway, Yang et al carried out a study and found that circCCDC66 played a role in the proliferation of VSMCs [91]. Through further investigation, they discovered that circCCDC66 promoted the expression of CCDC66, and CCDC66 suppression had the same effect as circCCDC66 deletion on the development and apoptosis of VSMCs.…”
Section: Circrna Microarray Profiling Of Mouse Aaas Induced Bymentioning
confidence: 99%
“…To prove the role of circRNA CCDC66 in the pathogenesis of AAAs and identify its corresponding pathway, Yang et al carried out a study and found that circCCDC66 played a role in the proliferation of VSMCs [ 91 ]. Through further investigation, they discovered that circCCDC66 promoted the expression of CCDC66, and CCDC66 suppression had the same effect as circCCDC66 deletion on the development and apoptosis of VSMCs.…”
Section: Verified Circrnas In Aaasmentioning
confidence: 99%
“…In the past decades, the functions of circRNAs in multiple biological progressions have been deeply studied, including cervical cancer [8][9][10][11][12]. Gao [17][18][19][20]. However, the role circ-CCDC66 in cervical cancer development is still uncovered.…”
Section: Introductionmentioning
confidence: 99%